User guide to the seedHealth model as part of the integrated seed health approach. RTB User Guide - Garrett, K.A.; Xing, Y. (International Potato Center, 2021)
Seed health is key to crop production and is a particular challenge for vegetatively propagated crops. Seedborne pathogens and pests can build up across generations in smallholder farmer fields when farmers save their own seed because high quality seed is too expensive or unavailable. Integrated seed health approaches and models address how best to combine management components: high quality seed, resistant varieties, and on-farm seed health management. To support integrated seed health approaches, a model of seed degeneration was developed for analysis of potential management scenarios. This model is available in an online interface and as the seedHealth package in the R programming environment. The model evaluates the risk of seed degeneration at a location or set of locations, based on factors such as weather conduciveness, crop disease resistance, and success rates for on-farm management such as positive selection and roguing. The model also evaluates how frequently high-quality seed purchase is likely needed to maintain acceptable yields. The seedHealth package is designed to support training and decision-making by researchers, policy makers, and practitioners. The online interface is particularly useful for training, to illustrates the likely outcomes from changing the three management components. The seedHealth package can also be used to evaluate the likely disease and yield outcomes for specific systems and user groups (e.g., gender or age groups), when sufficient data are available about seed degeneration rates and responses. The seedHealth package can be used for decision-support modeling by users who can develop or access estimates of seed degeneration rates for their systems. The open source code for seedHealth is designed to make the tool easy to modify to make new applications for the seed health community of practice.